MENUMBUHKAN PRODUKTIFITAS KERJA DENGAN TERNAK AYAM PADA EKS-ODGJ DI DESA DOHO KECAMATAN DOLOPO KABUPATEN MADIUN - Novita Erliana Sari; Dandi Hendrawan Wicaksono2 (UNIVERSITAS MUHAMMADIYAH METRO, 2020)
Since humans were born they have been faced with economic problems. Humans have an interest in fulfilling simple to complex needs. To make ends meet, it means that humans have to make sacrifices to work and produce something worthy of being sold. The process of producing something is what is meant by productivity. There are 14 ex-ODGJ in Dolopo District, all of whom do not have activities that aim to produce something with a sale value. This is due to the lack of public trust in the ex-ODGJ to produce anything. To answer this problem, the researchers took the initiative to carry out a simple study by providing a stimulus in the form of chickens to grow ODGJ productivity. The results obtained, 11 ODGJ were able to raise chickens well until harvest time. The conclusion in this study, activities in the form of chicken livestock can grow the productivity of ex-ODGJ in Doho Village, Dolopo District, Madiun Regency.Keyword: Activity, Work Productifity